Caregiver's burden in disorders of consciousness: a longitudinal study. (8th January 2016) - Covelli, V.; Sattin, D.; Giovannetti, A. M.; Scaratti, C.; Willems, M.; Leonardi, M.
Abstract : Objectives: To study the changes in the burden of informal caregivers of patients with disorders of consciousness (DOC) over time. Materials and methods: Short Form‐12, Family Strain Questionnaire, Beck Depression Inventory and Coping Orientations to Problem Experiences were administered. Results: Data collected on 216 informal caregivers of patients with DOC (59.6% females, mean age 53.4 ± 12.7 years old) were analysed at two time‐points (mean distance is 2.7 years). Results of the national study revealed that caregivers' mental health improved (T0: M = 41.1, SD = 11.8; T1: M = 45.8, SD = 11.7), whereas the emotional burden (T0: M = 7.4, SD = 3.6; T1: M = 6.6, SD = 3.9) and the presence of depressive symptoms (T0: M = 14.3, SD = 9.3; T1: M = 11.7, SD = 10.2) as well as the need for information about the disease (T0: M = 2.7, SD = 1.2; T1: M = 2.2, SD = 1.4), thoughts of death (T0: M = 3.6, SD = 1.5; T1: M = 3.1, SD = 1.6) and the use of avoiding coping strategy (T0: M = 7.8, SD = 1.0; T1: M = 6.0, SD = 1.3) decreased at T1. Furthermore, depressive symptoms positively correlated with the emotional burden (0.580) and negatively with the mental health component of caregivers' self‐perceived health condition (−0.473). Physical (−0.308) and mental health (−0.444) negatively correlated with emotional burden. Finally, the acute event and patients' health condition still have a deep impact on the economic situation of the family. Conclusion: Although high level of burden was observed, it tends to decrease over time, except for financial burden. Hence, this study suggests the importance to plan strategies or targeted interventions in order to reduce the psychosocial and financial burden associated with caregiving.